Sectoral foreign aid and income inequality - Saidon, Ruhaida; Yusop, Zulkornain; Ismail, Normaz Wana; Law, Siong Hook (Conference Master Resources, 2013)
This study contributes to the empirics of foreign aid and income inequality by investigating the effect of foreign aid on income inequality in recipient countries based on the disaggregation of foreign aid figures. For this purpose we include the four main sectoral foreign aid (social sector, production sector and multi sector) as determinants of income inequality. This study utilizied the Generalized Method of Moments (GMM) method for a panel of 75 foreign aid recipient countries covering the period of 1995-2009. The results indicated that different sectoral foreign aid affected income inequality differently. Aid to economic sector has significant impact in reducing the income inequality. In contrast, aid to multi sector significantly increased income inequality.